2018
DOI: 10.1103/physrevmaterials.2.075405
|View full text |Cite
|
Sign up to set email alerts
|

Electro-chemo-mechanical effects of lithium incorporation in zirconium oxide

Abstract: Understanding the response of functional oxides to extrinsic ion insertion is important for technological applications including electrochemical energy storage and conversion, corrosion, and electronic materials in neuromorphic computing devices. Decoupling the complicated chemical and mechanical effects of ion insertion is difficult experimentally. In this work, we assessed the effect of lithium incorporation in zirconium oxide as a model system, by performing first-principles based calculations. The chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…The Brouwer diagrams presented in this investigation that used Fermi-Dirac statistics gave subtle differences, with enhanced accuracy but do not fundamentally alter the picture previously reported in literature when considering no lithium [23]. The ability to stipulate a defect species concentration is novel to the Brouwer diagram script created by Murphy et al [30].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The Brouwer diagrams presented in this investigation that used Fermi-Dirac statistics gave subtle differences, with enhanced accuracy but do not fundamentally alter the picture previously reported in literature when considering no lithium [23]. The ability to stipulate a defect species concentration is novel to the Brouwer diagram script created by Murphy et al [30].…”
Section: Discussionmentioning
confidence: 70%
“…The Brouwer diagrams indicate that the oxygen vacancy concentration is increased by the presence of lithium. It has been previously reported that lithium, (๐ฟ๐ฟ๐ฟ๐ฟ ๐‘–๐‘– โ€ข ), can reduce the volume of both monoclinic and the tetragonal polymorphs [23]. By combining the volume changes from all defect concentrations included in the Brouwer diagrams with constant pressure calculations that allow for volumetric relaxation, a small reduction in volume for the monoclinic polymorph was observed with a minimal effect to the tetragonal polymorph.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation